Spring Into Wellness: An ACOG District VI Initiative [4M]. (May 2018) - Barnard, Emily; Zeal, Carley; Mallen, Adrianne; Hall, Evelyn; Lyerly, Kristin; Brincat, Cynthia
Abstract : INTRODUCTION: In the setting of physician shortages and increasing burnout, we sought to challenge the historically competing interests of wellness and residency. The aim of our project, Spring Into Wellness, was to foster well-being in our District while encouraging community and collaboration between residency programs. METHODS: Prior to initiating the project, we used the WHO-5 Well Being Index, a validated assessment tool measuring five aspects of wellness, to survey Junior Fellows in Training (JFs) from ACOG District VI. A JF Wellness committee planned weekly themes during April 2017, highlighting Nutritional, Emotional, Physical, and Community Wellness. Daily e-mails encouraged participation which was tracked using postings on social media (Facebook®). Funding for weekly winning residency programs was provided by Fellows in District VI. RESULTS: 110 out of 466 eligible residents completed surveys (23.6%). More than half of the time JFs were "interested" in their work (76.4%) and "felt cheerful" (77.3%). However, less than half of the time 78.0% "woke up feeling fresh and rested" and 67.9% "felt active and vigorous." 8 of 24 programs participated in wellness month, posting 72 entries on social media. Three winning programs received cash prizes. Social media posts declined from week one (23) to week four (0). CONCLUSION: A wellness initiative meets an obvious need in JF training programs. While our program met with initial enthusiasm, as the month progressed this waned. Our initiative is accessible and could translate to other Districts and residencies. Future improvements include transitioning to a condensed wellness week, a follow up survey, and encouraging faculty participation.